Fms-like tyrosine kinase 3 receptor ligand (Flt3L)-based vaccination administered with an adenoviral vector prevents tumor growth of colorectal cancer in a BALB/c mouse model - Riediger, Carina; Wingender, Gerhard; Knolle, Percy; Aulmann, Sebastian; Stremmel, Wolfgang; Encke, Jens (Journal of cancer research and clinical oncology, 2013)
Colorectal cancer is the third most frequent cancer in industrial nations. Therapeutic strategies to treat metastatic disease and prevent recurrence are needed. Anti-tumor immunity can be induced by dendritic cells. Dendritic cells can be expanded by the fms-like tyrosine kinase 3 ligand (Flt3L) in vivo. The aim of this study was to develop an adenoviral-based immune-gene therapy of colorectal cancer with Flt3L in a BALB/c mouse model.
Gesehen am 12.01.2022